Multicenter results of long-limb bypass reconstruction after gastrectomy in patients with gastric cancer and type II diabetes - Jong-Han Kim; Yeon-Ju Huh; Susan Park; Young Suk Park; Do Joong Park; Jin-Won Kwon; Joo Ho Lee; Yoon Seok Heo; Seung Ho Choi (Asian Journal of Surgery, 2020)
Summary: Background/Objective: The number of gastric cancer and type II diabetes mellitus is increasing in Korea. Metabolic surgery could be extended to gastric cancer patients with type II diabetes, especially those who are expected to achieve long-term survival. This study aimed to investigate change of diabetic status in patients undergoing long-limb Roux-en-Y bypass reconstruction compared with conventional Billroth II after curative gastrectomy. In total, 130 patients from five university hospital centers underwent long-limb Roux-en Y reconstruction after radical distal gastrectomy. Methods: In the long-limb group, the length of biliopancreatic limbs was more than 80 cm, and the length of the Roux limb was more than 80 cm. The control group comprised 96 patients who underwent conventional Billroth II reconstruction after distal gastrectomy. Follow-up data at three, six, nine, and 12 months were compared between the two groups. Results: Fasting blood sugar (FBS) and hemoglobin (Hb) A1c levels decreased more significantly in the long-limb Roux-en-Y group (FBS: 28.8 mg/dL; HbA1c: 0.72%). However, decreases in body mass index, albumin, and hemoglobin did not differ significantly between the two groups. Diabetes control significantly improved in the long-limb group. In multivariate analysis, long-limb bypass reconstruction was the significant factor for glycemic outcomes. Conclusion: Roux-en-Y bypass with increased length of limbs after gastrectomy shows a favorable glycemic control for gastric cancer patients with type II diabetes without nutritional deficit and anemia. To obtain future perspectives, large-scale prospective studies with long-term outcomes are needed. Keywords: Type II DM, Gastric cancer, Long limb Roux-en Y